Disordered Punishment: Workaround Technologies of Criminal Records Disclosure and the Rise of a New Penal Entrepreneurialism - Corda, Alessandro (The British journal of criminology, 2020)
The privatization of punishment is a well-established phenomenon in modern criminal justice operations. Less understood are the market and technological forces that have dramatically reshaped the creation and sharing of criminal record data in recent years. Analysing trends in both the United States and Europe, we argue that this massive shift is cause to reconceptualize theories of penal entrepreneurialism to more directly address the role of technology and commercial interests. Criminal records, or proxies for them, are now actively produced and managed by third parties via corporate decision-making processes, rather than government dictating boundaries or outsourcing duties to private actors. This has led to what we term ‘disordered punishment', imposed unevenly and inconsistently across multiple platforms, increasingly difficult for both government and individuals to control.